Budżetowanie kosztów projektów badawczo-rozwojowych (projekty realizowane w Programach Ramowych Unii Europejskiej) - Piotrowska, Katarzyna (Cost Budgeting of the Research and Development Projects (Projects that are Implement under the European Union Framework Programmes)., 2006)
The modern worldwide economic progress proceeds according to the scientific and technical revolution lows. That is why reaching the financial success depends on the proper realization of the stages that precedes the innovation: research and development in the economic entity. However, the research and development operations are very expensive, and economic profits undoubtedly bring profits, but only in the future. The main ain of this article is to present the cost budgeting problems, which are borne according to research and development projects that are implemented by economic entities (especially in the small and medium entities). Additionally this article contains forms with numerical data and budgetary forms, that were proposed by the author of this article. The forms with numerical data were used by economic entity, which has implemented the 5th European Union Framework Programme.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1101, s. 116-126